2023
DOI: 10.3389/fnut.2023.1063534
|View full text |Cite
|
Sign up to set email alerts
|

Association between the uric acid to high density lipoprotein cholesterol ratio and alanine transaminase in Chinese short stature children and adolescents: A cross-sectional study

Abstract: ObjectiveUric acid to high-density lipoprotein cholesterol ratio (UHR), the ratio of uric acid to high-density lipoprotein cholesterol, is a newly proposed marker of metabolic abnormalities. There are few previous studies directly investigating the relationship between UHR and alanine aminotransferase (ALT), especially in short stature populations, however, short stature children and adolescents are more likely to have metabolic disorders. This research aimed to investigate the relationship between the UHR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[19] Additionally, there is emerging evidence suggesting a potential association between UHR and the regulation of ALT levels in Chinese children and adolescents with short stature. [20]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Additionally, there is emerging evidence suggesting a potential association between UHR and the regulation of ALT levels in Chinese children and adolescents with short stature. [20]…”
Section: Discussionmentioning
confidence: 99%
“…[19] Additionally, there is emerging evidence suggesting a potential association between UHR and the regulation of ALT levels in Chinese children and adolescents with short stature. [20] UHR is a marker combining UA and HDL-C. Thus, increased UHR is caused by either decreased serum HDL cholesterol, increased serum UA, or both.…”
Section: Exposurementioning
confidence: 99%
“…The uric acid (UA) to high-density lipoprotein cholesterol (HDL-C) ratio (UHR), a novel marker indicating metabolic and in ammatory conditions, has been linked to an increased risk of different illnesses in previous research and has been demonstrated to have the ability to serve as a predictor for several clinical outcomes [17][18][19][20]. Xie et al discovered that high UHR levels were independently linked to the risk and severity of nonalcoholic fatty liver disease in the American population, with varying correlations based on gender [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies have suggested that utilizing these risk factors to identify and predict the likelihood of developing osteoporosis is an e cacious method for early prevention and screening [15, 16]. Therefore, there is a growing emphasis on investigating the factors linked to osteoporosis in current research.The uric acid (UA) to high-density lipoprotein cholesterol (HDL-C) ratio (UHR), a novel marker indicating metabolic and in ammatory conditions, has been linked to an increased risk of different illnesses in previous research and has been demonstrated to have the ability to serve as a predictor for several clinical outcomes [17][18][19][20]. Xie et al discovered that high UHR levels were independently linked to the risk and severity of nonalcoholic fatty liver disease in the American population, with varying correlations based on gender [20].…”
mentioning
confidence: 99%